Meningkatkan Hasi Belajar Matematika melalui Model Snowball Throwing Kelas V SD Ade Irma Suryani Sei Rotan - Emy Hariati (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
Mathematics lessons are considered difficult because some students do not understand mathematical concepts so they feel bored and bored. The cause of low mathematics learning outcomes is because students are often sleepy during math lessons in the last hour. The purpose of this study is to improve mathematics learning outcomes through the Snowball Throwing learning model for the fifth grade of SD Ade Irma Suryani Sei Rotan T.A. 2021-2022. This type of research is classroom action (CAR). The cycle is carried out through 4 stages, namely planning, implementation, observation, and reflection. Data was collected through observation and tests, using quantitative and qualitative analysis techniques. The subjects in this study were class V students, totaling 20 students. Based on data analysis that the increase in student learning outcomes in the pre-cycle the average value is 67.1 with a sufficient category. In the first cycle after the action, the average value was 71.3 with a good category and an increase of 8.99. In the second cycle there was an increase of 3.35 with a cumulative average value of 74.76 in the good category. Keywords: Learning Outcomes; Mathematics; Snowball Throwing Models